Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Di Restoran APJ Yos Sudarso Kota Medan - Sianturi, Irvan Sudarto; Siagian, Nalom; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
In this era of increasing globalization, the business world is developing very rapidly, one of which is business in the culinary sector, the number of businesses emerging has resulted in an increase in the number of businesses of a similar nature, causing increasingly fierce competition. Business actors are required to be able to maintain the needs and desires of their customers. By understanding customer needs and desires, this will provide important input for the company. This research was carried out using quantitative methods, meaning that the research was carried out on certain representative populations and samples. The research results show that Service Quality (X1) has a positive and significant effect on Consumer Purchasing Decisions (Y). Price (X2) has a positive and significant effect on Customer Satisfaction. Meanwhile, the results of the simultaneous test (F Test) in table 4.17 above, can be seen that the Fcount value is 188.868 where > from Ftable is 3.09 and the significance value is 0.000 which means <0.05. So it can be concluded that the independent variables (Service Quality and Price) simultaneously influence Customer Satisfaction.